2021
DOI: 10.2147/opth.s272328
|View full text |Cite
|
Sign up to set email alerts
|

Macular Vessel Density in Diabetic Retinopathy Patients: How Can We Accurately Measure and What Can It Tell Us?

Abstract: Diabetic retinopathy is one of the leading causes of blindness worldwide. Optical coherence tomography angiography (OCTA) is a non-invasive technology that provides depth-resolved images of the chorioretinal vasculature and allows for the understanding of the changes in vasculature with diabetic retinopathy. Not only can it provide qualitative information, but OCTA can also provide quantitative information about the vasculature in patients with diabetic retinopathy. Macular vessel density is one of the quantit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 79 publications
1
15
0
Order By: Relevance
“…There is a wealth of OCTA literature in DR, and numerous studies that have reported reduced VD, SVD, and FD in patients with DR. 2 4 , 10 It is also known that older age is associated with decreased VD and SVD. 5 , 19 This is consistent with our findings that PDR and older age were most frequently significantly associated with decreased values of VD, SVD, and FD, which served as somewhat of a positive control in our study to evaluate which combinations of preprocessing and binarization algorithms might be most accurate.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…There is a wealth of OCTA literature in DR, and numerous studies that have reported reduced VD, SVD, and FD in patients with DR. 2 4 , 10 It is also known that older age is associated with decreased VD and SVD. 5 , 19 This is consistent with our findings that PDR and older age were most frequently significantly associated with decreased values of VD, SVD, and FD, which served as somewhat of a positive control in our study to evaluate which combinations of preprocessing and binarization algorithms might be most accurate.…”
Section: Discussionsupporting
confidence: 90%
“…The values of these metrics have been shown to be altered in retinal vascular disease, such as diabetic retinopathy (DR). 1 5 …”
Section: Introductionmentioning
confidence: 99%
“…There are other OCTA metrics that were reported in the literature, such as vessel or perfusion density, vessel area density, and skeletonized vessel density or vessel length index [19,20,[41][42][43][44][45]. They were evaluated to assess the integrity (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…These methods cover automatic or semi-automatic segmentation algorithms designed on both the macro and micro macula's vasculature levels. Some researchers suggested extending the OCTA segmentation tasks by producing quantification parameters [17,19,20,[41][42][43][44][45], such as OCTA vessels' length, area density, and diameters. Some studies moved beyond the segmentation and quantitative analysis toward exploring the use of Artificial Intelligence (AI) techniques such as Deep Learning [21-23, 46, 48] and Machine Learning [24,47] to classify the delineated vasculature regions into normal or abnormal.…”
Section: Introductionmentioning
confidence: 99%
“…Vascular length density (VLD) index was calculated as the area of pixels occupied with skeletonized vessels divided by the total area of the image. In skeletonization, reducing the width of each vessel to a single pixel results in uniform contribution of the large and small vasculature in density measurements 19 .…”
Section: Methodsmentioning
confidence: 99%